On the development of an ultra-high-capacity tensiometer capable of measuring water tensions to 7 MPa. Issue 6 (2nd August 2018) - Mendes, J.; Gallipoli, D.; Tarantino, A.; Toll, D.
Abstract : Tensiometers are increasingly used in geotechnical engineering to monitor pore-water tension in the field and to study the hydro-mechanical behaviour of unsaturated soils in the laboratory. Early tensiometers exhibited a relatively small measuring range, typically limited to a tension of 0·1 MPa, due to the breakdown of water tension inside the sensing unit at absolute negative pressures. This limitation was subsequently overcome by the design of high-capacity tensiometers (HCTs), which enabled the measurement of considerably larger pore-water tensions. According to the literature, the highest value of water tension ever recorded by an HCT is 2·6 MPa. In the present work, this value is almost tripled by designing a novel ultra-high-capacity tensiometer (UHCT) capable of recording water tensions up to 7·3 MPa. This is achieved by replacing the traditional ceramic interface with a nanoporous glass (typically employed by physicists for the study of confined liquids), which has never been used before in the manufacture of tensiometers. The maximum attainable tension has been determined using tests where the UHCT measurement was progressively increased by vaporising water from the glass interface until the occurrence of tension breakdown (often referred to as 'heterogeneous cavitation' or 'tensiometer cavitation'). The increased measuring range and the potentially larger measuring stability of the proposed UHCT will contribute to enhance laboratory testing of soils at high suctions and long-term monitoring of earth structures.